Pneumonia Caused by Klebsiella spp. in 46 Horses - Estell, K.E. (J Vet Intern Med, 2016)
BACKGROUND: Klebsiella spp. are implicated as a common cause of bacterial pneumonia in horses, but few reports describe clinical presentation and disease progression. HYPOTHESIS/OBJECTIVES: To describe the signalment, clinicopathologic data, radiographic and ultrasonographic findings, antimicrobial susceptibility, outcome, and pathologic lesions associated with Klebsiella spp. pneumonia in horses. ANIMALS: Forty‐six horses from which Klebsiella spp. was isolated from the lower respiratory tract. METHODS: Retrospective study. Medical records from 1993 to 2013 at the William R. Pritchard Veterinary Medical Teaching Hospital, University of California, Davis were reviewed. Exact logistic regression was performed to determine if any variables were associated with survival to hospital discharge. RESULTS: Survival in horses <1 year old was 73%. Overall survival in adults was 63%. For adults in which Klebsiella pneumoniae was the primary isolate, survival was 52%. Mechanical ventilation preceded development of pneumonia in 11 horses. Complications occurred in 25/46 horses, with thrombophlebitis and laminitis occurring most frequently. Multi‐drug resistance was found in 47% of bacterial isolates. Variables that significantly impacted survival included hemorrhagic nasal discharge, laminitis, and thoracic radiographs with a sharp demarcation between marked caudal pulmonary alveolar infiltration and more normal‐appearing caudodorsal lung. CONCLUSIONS AND CLINICAL IMPORTANCE: Klebsiella spp. should be considered as a differential diagnosis for horses presenting with hemorrhagic pneumonia and for horses developing pneumonia after mechanical ventilation. Multi‐drug resistance is common. Prognosis for survival generally is fair, but is guarded for adult horses in which K. pneumoniae is isolated as the primary organism.